In The Between - Egeran Art Advisory, Istanbul (Istanbul : Egeran Art Advisory, 2009)
Alptekin, Hüseyin Bahri ; Coffin, Peter ; Creed, Martin ; Friedman, Martha ; Friedman, Tom ; Al-Hadid, Diana ; Kazma, Ali ; Marclay, Christian ; Navarro, Ivan ; Ogut, Ahmet ; Evans, Cerith Wyn
In The Between, Egeran Art Advisory, Istanbul, 10 September - 10 October 2009
boek